2021
DOI: 10.1038/s41598-021-82346-6
|View full text |Cite
|
Sign up to set email alerts
|

B-cells expressing NgR1 and NgR3 are localized to EAE-induced inflammatory infiltrates and are stimulated by BAFF

Abstract: We have previously reported evidence that Nogo-A activation of Nogo-receptor 1 (NgR1) can drive axonal dystrophy during the neurological progression of experimental autoimmune encephalomyelitis (EAE). However, the B-cell activating factor (BAFF/BlyS) may also be an important ligand of NgR during neuroinflammation. In the current study we define that NgR1 and its homologs may contribute to immune cell signaling during EAE. Meningeal B-cells expressing NgR1 and NgR3 were identified within the lumbosacral spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…In the cerebellum, the proinflammatory cytokines IL1β and IL6 were reduced in Fgfr1 ind−/− mice at day 62 p.i. Cytokines play a key role in recruiting activated immune cells into the CNS [40][41][42]. IL1β plays a role in neuronal degeneration via p53-mediated apoptosis of neurons [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the cerebellum, the proinflammatory cytokines IL1β and IL6 were reduced in Fgfr1 ind−/− mice at day 62 p.i. Cytokines play a key role in recruiting activated immune cells into the CNS [40][41][42]. IL1β plays a role in neuronal degeneration via p53-mediated apoptosis of neurons [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been revealed that there is a correlation between BAFF and Nogo receptor (NgR) signaling complex [75], a member of the leucine rich repeat (LRR) superfamily [76], that binds with high affinity and may potentially function as a BAFF receptor [48,77]. The NgR signaling complex consists of NgR1, the co-receptor LINGO-1 and the neurotrophin receptor p75 (p75NTR) or TROY receptor and it mediates its inhibitory effect against axonal regeneration through binding to Nogo 66 with nanomolar affinity [78][79][80].…”
Section: Ngr Complex Signaling Pathways Interaction With Various Componentsmentioning
confidence: 99%
“…The NgR signaling complex consists of NgR1, the co-receptor LINGO-1 and the neurotrophin receptor p75 (p75NTR) or TROY receptor and it mediates its inhibitory effect against axonal regeneration through binding to Nogo 66 with nanomolar affinity [78][79][80]. This receptor complex binds with myelin associated inhibitory factors (MAIFs), which are myelin-associated glycoprotein (MAG), oligodendrocyte-myelin glycoprotein (OMgp) and Nogo-A and are found on myelin sheath of oligodendrocytes [77,81,82]. Nogo-A is one of the three splice variants (Nogo A, B and C), that have a conserved extracellular region of 66 amino acids [80,83], which is found between two transmembrane helices allowing the molecule to anchor to the oligodendrocyte membrane [81].…”
Section: Ngr Complex Signaling Pathways Interaction With Various Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble BAFF (sBAFF) is formed from the hydrolysis of membrane-type BAFF and can improve the activity of B cells, CD4+T cells, and NK cells to increase the body's immune responses [30]. Three kinds of the receptors of BAFF have been reported, they are B-cell maturation antigen (BCMA), BAFF receptor 3 (BR3), and trans-membrane activator and calcium modulator and cyclophilin ligand interactor (TACI) [2,[31][32][33][34][35][36][37][38][39][40][41]. Although BAFF often functions as a homo-trimer form, a more active BAFF 60-mer has been reported [42].…”
Section: Introductionmentioning
confidence: 99%